2020
DOI: 10.1038/s41416-020-0964-x
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of p16INK4a expression as a single marker to select patients with HPV-driven oropharyngeal cancers for treatment de-escalation

Abstract: Background A remarkably better prognosis is associated with oropharyngeal squamous cell carcinomas (OPSCC) driven by human papillomaviruses (HPV) compared with HPV-negative OPSCC. Consequently, de-escalation of standard treatment has been suggested. Due to modest specificity rates, debates are ongoing, whether p16INK4a, a surrogate marker for HPV-driven OPSCC, is sufficient to correctly identify those tumours and avoid substantial HPV misattribution and thus undertreatment of patients by de-esc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 28 publications
0
40
0
5
Order By: Relevance
“…At present, a large number of foreign studies have shown that the sensitivity and specificity of a single test cannot be used to qualitatively diagnose malignant tumors. The main reason is that tumor cells and normal tissues can express certain genes (23). Studies have suggested that the combined detection of imaging and molecular biology can improve the diagnosis of malignant diseases, but there is no final conclusion (24).…”
Section: A B C D Ementioning
confidence: 99%
“…At present, a large number of foreign studies have shown that the sensitivity and specificity of a single test cannot be used to qualitatively diagnose malignant tumors. The main reason is that tumor cells and normal tissues can express certain genes (23). Studies have suggested that the combined detection of imaging and molecular biology can improve the diagnosis of malignant diseases, but there is no final conclusion (24).…”
Section: A B C D Ementioning
confidence: 99%
“…The overexpression of p16 Ink4a (p16 + ) has, similar to the presence of HPV-DNA (HPVDNA + ), been shown to have a strong correlation to active HPV infection (i.e., expression of HPV E6 mRNA) in OPSCC, although the combined presence of both p16 + and HPVDNA + is superior to using these markers separately [ 13 ]. Because p16 + is easier to determine by immunohistochemistry (IHC), it was therefore suggested as a possible surrogate marker for HPV infection, and thereby also shown to be associated with a better prognosis in OPSCC [ 14 , 15 ]. In addition, p16 + as a marker of HPV infection is now used in the 8th version of the American Joint Committee of Cancer (AJCC) AJCC Staging manual (TNM-8) to separate HPV-related from HPV-unrelated OPSCC [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to other head and neck cancers, the incidence of OPSCC is increasing and in many countries a growing number of cases are attributed to high‐risk human papillomavirus (HPV) 2–4 . These patients are characterized by a specific risk profile, comparatively good response to therapy, and superior overall survival (OS) rates 5,6 . Consequently, strategies to de‐escalate the treatment of patients with HPV‐driven (HPV+) OPSCC are investigated.…”
Section: Introductionmentioning
confidence: 99%